Conditional transgenic expression of PIM1 kinase in prostate induces inflammation-dependent neoplasia. - Maja Narlik-Grassow; Carmen Blanco-Aparicio; Yolanda Cecilia; Marco Perez; Sandra Muñoz-Galvan; Marta Cañamero; Oliver Renner; Amancio Carnero (PLoS ONE, 2013)
The Pim proteins are a family of highly homologous protein serine/threonine kinases that have been found to be overexpressed in cancer. Elevated levels of Pim1 kinase were first discovered in human leukemia and lymphomas. However, more recently Pim1 was found to be increased in solid tumors, including pancreatic and prostate cancers, and has been proposed as a prognostic marker. Although the Pim kinases have been identified as oncogenes in transgenic models, they have weak transforming abilities on their own. However, they have been shown to greatly enhance the ability of other genes or chemical carcinogens to induce tumors. To explore the role of Pim1 in prostate cancer, we generated conditional Pim1 transgenic mice, expressed Pim1 in prostate epithelium, and analyzed the contribution of PIM1 to neoplastic initiation and progression. Accordingly, we explored the effect of PIM1 overexpression in 3 different settings: upon hormone treatment, during aging, and in combination with the absence of one Pten allele. We have found that Pim1 overexpression increased the severity of mouse prostate intraepithelial neoplasias (mPIN) moderately in all three settings. Furthermore, Pim1 overexpression, in combination with the hormone treatment, increased inflammation surrounding target tissues leading to pyelonephritis in transgenic animals. Analysis of senescence induced in these prostatic lesions showed that the lesions induced in the presence of inflammation exhibited different behavior than those induced in the absence of inflammation. While high grade prostate preneoplastic lesions, mPIN grades III and IV, in the presence of inflammation did not show any senescence markers and demonstrated high levels of Ki67 staining, untreated animals without inflammation showed senescence markers and had low levels of Ki67 staining in similar high grade lesions. Our data suggest that Pim1 might contribute to progression rather than initiation in prostate neoplasia.